Back Cover: Global analysis of phosphoproteome dynamics in embryonic development of zebrafish (Danio rerio). Issue 1 (5th January 2016) - Kwon, Oh Kwang; Kim, Sun Ju; Lee, You‐Mie; Lee, Young‐Hoon; Bae, Young‐Seuk; Kim, Jin Young; Peng, Xiaojun; Cheng, Zhongyi; Zhao, Yingming; Lee, Sangkyu
Abstract : DOI:10.1002/pmic.201500017 The 3500 non‐redundant phosphorylation sites on 2166 phosphoproteins and 1564 quantified have been reported during the development of zebrafish embryos, which is the largest dataset for phosphoproteins in zebrafish. The GO enrichment of dynamic phosphoproteomics indicated the various regulatory processes involved in each development stage. For details, see the article by Oh Kwang Kwon et al. on page 136.